Զաքարիա վարդապետ Վաղարշապատցին եւ նրա նորայայտ դամբարանը Մայր Աթոռ Ս. Էջմիածնում - Յարութիւնեան, Արսէն; Բադիշեան, Ամիրան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
23 декабря 2019 года при демонтаже плиточного настила вокруг колокольни Кафедрального собора Святого Эчмиадзина, на расстоянии 8,85 м к западу от входа в колокольню и на глубине около 0,60 м от уровня плит был обнаружен саркофаг с гладко вытесанным надгробным камнем, с высеченной на нем надписью. Согласно эпитафии, здесь покоится скончавшийся в 1659 году Закария Вардапет (архимандрит). On December 23, 2019, while dismantling the tile floor around the bell tower of the Cathedral of Holy Etchmiadzin, at a distance of 8.85 m west of the entrance to the bell tower and at a depth of about 0.60 m from the level of the slabs, a sarcophagus with a smoothly carved tombstone and a commemorative inscription was found. According to the epitaph, Archimandrite Zakaria, who died in 1659, was buried there.
Keywords: Armenian church; Biography